A measurement of parity-violating asymmetry in polarized cold neutron capture on 3He. (December 2020) - McCrea, M
Abstract: The n3He experiment measured the parity-violating directional asymmetry in the proton emission direction relative to the initial neutron polarization in the capture of polarized cold neutrons in the reaction n + 3 He → T + p . Data taking was completed at the end of 2015 at the SNS, and two independent analyses of the proton parity asymmetry have since been completed and are in agreement. I will present the methods used to calculate the asymmetry, and the final results of the experiment.